SUSTAINABLE SOLUTIONS: GREENHOST LEADING THE INDUSTRIAL DAY 6.0 CHARGE - Utik Kuntariati; Luh Eka Susanti; A. A. A. Arun Suwi Arianty; Putu Dian Yuliani Paramita; Ni Made Rinayanthi; I Wayan Suadnyana (Sewagati, 2024)
Sustainable Solutions: Greenhost Leading the Industrial Day 6.0 Charge" aims to promote sustainability in the accommodation sector, particularly through the implementation of green practices in hotels and other lodgings. This article presents the methodology and outcomes of a community engagement initiative conducted at the International Institute of Tourism and Business. Through collaborative efforts, including needs assessment, joint action planning, training sessions, environmental assessments, and program development, the project aimed to enhance awareness and adoption of eco-friendly practices. Key findings highlight the importance of collaboration, tailored training, and targeted environmental assessments in advancing sustainability goals in the accommodation industry.